The Relationship Between Satisfaction With Life and Depression Symptoms by Gender - Gigantesco, Antonella; Fagnani, Corrado; Toccaceli, Virgilia; Stazi, Maria Antonietta; Lucidi, Fabio; Violani, Cristiano; Picardi, Angelo (Frontiers in Psychiatry, 2019)
Depression is a worldwide public health concern. The World Health Organization (WHO) has recently recommended the implementation of programs for strengthening subjective well-being (SWB) to reduce mental disorders, including depression. Also, in 2013, European member-states agreed on a single measure of SWB, i.e., life satisfaction, for monitoring the progress of SWB in the WHO health policy framework, ‘Health 2020’. Life satisfaction is strongly associated with depression, therefore, its use as health indicator could be suitable to identify individuals at risk for depression. Critical, to this use of life satisfaction to target also depression is knowledge on the nature of the association between the two throughout the lifespan and by gender. This study aims at contributing to the knowledge about this association in a sample of 51 individuals screened for Major Depressive Disorder (MDD) and Dysthymic Disorder (Dys). All individuals were administered the Primary Care Screener for Affective Disorders and the Satisfaction With Life Scale (SWLS). Among individuals negative for MDD or Dys, women displayed similar satisfaction compared with men, whereas among individuals positive for MDD or Dys, women showed greater satisfaction compared with men, whose score denoted life dissatisfaction. Consistently, the regression model for SWLS revealed a significant main effect of positivity for MDD or Dys on life satisfaction as well as a significant interaction between positivity for MDD or Dys and gender. The results of this study do not support the notion that satisfaction with life and depressive symptoms could belong to highly related dimensions, at least among females.